FINANCIAL MANAGEMENT STRATEGY IN EDUCATIONAL INSTITUTIONS FOR RESOURCE OPTIMIZATION AND OPERATIONAL EFFICIENCY - Sudana Sudana (International Journal of Teaching and Learning, 2025)
Effective financial management is a vital component that influences the quality of education and financial health of educational institutions. Appropriate and planned funding allocation allows institutions to improve facilities, teaching competencies, and develop innovative educational programs, all of which contribute to improving the quality of education. Additionally, efficient financial management ensures the stability and financial health of institutions, helping them avoid budget deficits as well as building emergency fund reserves for unforeseen situations. Discipline in financial management also expands educational accessibility through the provision of scholarships and financial assistance for underprivileged students and ensures the sustainability and relevance of institutions in the long term. Therefore, wise financial management not only supports daily operations but also plays an essential role in realizing the long-term vision and mission of educational institutions.